Disruption of the Pseudomonas aeruginosa Tat system perturbs PQS-dependent quorum sensing and biofilm maturation through lack of the Rieske cytochrome bc₁ sub-unit - Soh, Eliza Ye-Chen (2022)
Extracellular DNA (eDNA) is a major constituent of the extracellular matrix of Pseudomonas aeruginosa biofilms and its release is regulated via pseudomonas quinolone signal (PQS) dependent quorum sensing (QS). By screening a P. aeruginosa transposon library to identify factors required for DNA release, mutants with insertions in the twin-arginine translocation (Tat) pathway were identified as exhibiting reduced eDNA release, and defective biofilm architecture with enhanced susceptibility to tobramycin. P. aeruginosa tat mutants showed substantial reductions in pyocyanin, rhamnolipid and membrane vesicle (MV) production consistent with perturbation of PQS-dependent QS as demonstrated by changes in pqsA expression and 2-alkyl-4-quinolone (AQ) production. Provision of exogenous PQS to the tat mutants did not return pqsA, rhlA or phzA1 expression or pyocyanin production to wild type levels. However, transformation of the tat mutants with the AQ-independent pqs effector pqsE restored phzA1 expression and pyocyanin production. Since mutation or inhibition of Tat prevented PQS-driven auto-induction, we sought to identify the Tat substrate(s) responsible. A pqsA::lux fusion was introduced into each of 34 validated P. aeruginosa Tat substrate deletion mutants. Analysis of each mutant for reduced bioluminescence revealed that the primary signalling defect was associated with the Rieske iron-sulfur subunit of the cytochrome bc1 complex. In common with the parent strain, a Rieske mutant exhibited defective PQS signalling, AQ production, rhlA expression and eDNA release that could be restored by genetic complementation. This defect was also phenocopied by deletion of cytB or cytC1. Thus, either lack of the Rieske sub-unit or mutation of cytochrome bc1 genes results in the perturbation of PQS-dependent autoinduction resulting in eDNA deficient biofilms, reduced antibiotic tolerance and compromised virulence factor production.